Fixed points for a pair of weakly compatible mappings satisfying a new type of ϕ - implicit relation in S - metric spaces - Popa Valeriu; Patriciu Alina-Mihaela (Acta Universitatis Sapientiae: Mathematica, 2020)
The purpose of this paper is to introduce a new type of φ -implicit relation in S - metric spaces and to prove a general fixed point for a pair of weakly compatible mappings, which generalize Theorems 1, 2, 4 [23], Theorems 1-7 [13], Corollary 2.19 [13], Theorems 2.2, 2.4 [19], Theorems 3.2, 3.3, 3.4 [20] and other known results.